Rapid Detection of Fibrinopeptides by Bidimensional Paper Electrophoresis - Stocker, K; Straub, P. W; Eckert, B (Thrombosis and Haemostasis, 1970)
A simplified method for the rapid identification of the fibrinopeptides in small amounts of supernatants of fibrin clots is described.Using this method, we confirmed the earlier observation that Reptilase-R, a thrombin-like enzyme from the venom of Bothrops atrox, exclusively liberates fibrinopeptides A and AP. It was further demonstrated that fibrinopeptide B can be rapidly isolated from small amounts of fibrinogen or even of plasma by thrombin action on washed Reptilase clots.